Temperament, behavior and painful experience in the child developmental course - Klein, Vivian Caroline; Linhares, Maria Beatriz Martins (Paidéia (Ribeirão Preto), 2007)
The objective of the present study was to review the studies about the relations among the temperament, behavior, and early painful experiences in children developmental pathways, especially with preterm born children. The empirical studies were obtained through the data bases PsycINFO and Medline. The results showed that the temperament was a predictor of the individual patterns of reaction to pain and to behavior problems at different ages. Moreover, the early painful experiences of children born preterm can influence infant's reactivity, which was in association to temperamental dimensions during the first years of life.